Kosakata dalam Keterampilan Berbicara Bahasa Arab: Analisis Peranan Bagi Pelajar Tingkat Pemula - Isnaini, Anisah (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2022)
This research aims to analyze the role of vocabulary in Arabic speaking skills for beginners. The study employs a qualitative approach with a literature review method focusing on scholarly literature addressing the topic. Data sources include scholarly literature such as reference books and published journal articles. Content analysis is used for data analysis. The research results indicate that knowing and mastering vocabulary plays a crucial role in helping and enriching the communication of ideas. For beginners, a rich and adequate vocabulary enables students to express ideas and communicate effectively. Furthermore, students with a broad vocabulary feel more confident and fluent in speaking across various contexts.